The Conditions of Immanent Critique. Issue 1 (2nd January 2022) - Procyshyn, Alexei
ABSTRACT: This article contributes to methodological debates in contemporary critical theory regarding the scope and features of immanent critique. I spell out the philosophical commitments presupposed by this approach to criticism and identify its basic features by comparing it with more recognizable argumentative or interpretative strategies. This comparison yields three immanent-critical requirements – for inherence, contradiction, and access – which bring into relief the heuristic and ampliative character of immanent criticism. Yet, these requirements also imply that "immanent critique" is not a method in any strict sense, since they are multiply interpretable and hence generative of distinctive critical comportments.